HIV alters neuronal mitochondrial fission/fusion in the brain during HIV-Associated Neurocognitive Disorders - Fields, Jerel Adam (Neurobiol Dis, 2015)
HIV-associated neurocognitive disorders (HAND) still occur in approximately 50% of HIV patients, and therapies to combat HAND progression are urgently needed. HIV proteins are released from infected cells and cause neuronal damage, possibly through mitochondrial abnormalities. Altered mitochondrial fission and fusion is implicated in several neurodegenerative disorders. Here, we hypothesized that mitochondrial fission/fusion may be dysregulated in neurons during HAND. We have identified decreased mitochondrial fission protein (dynamin 1-like; DNM1L) in frontal cortex tissues of HAND donors, along with enlarged and elongated mitochondria localized to the soma of damaged neurons. Similar pathology was observed in the brains of GFAP-gp120 tg mice. In vitro, recombinant gp120 decreased total and active DNM1L levels, reduced the level of Mitotracker staining, and increased extracellular acidification rate (ECAR) in primary neurons. DNM1L knockdown enhanced the effects of gp120 as measured by reduced Mitotracker signal in the treated cells. Interestingly, overexpression of DNM1L increased the level of Mitotracker staining in primary rat neurons and reduced neuroinflammation and neurodegeneration in the GFAP-gp120-tg mice. These data suggest that mitochondrial biogenesis dynamics are shifted towards mitochondrial fusion in brains of HAND patients and this may be due to gp120-induced reduction in DNM1L activity. Promoting mitochondrial fission during HIV infection of the CNS may restore mitochondrial biogenesis and prevent neurodegeneration.